Pengembangan Instrumen Persepsi Remaja terhadap Peran Orangtua sebagai Pendidik Iman dalam Keluarga Kristen berdasarkan Ulangan 6:6-9 - Sari, Ganda; Siahaan, Mery Fuji (Universitas Pelita Harapan, 2025)
This study aims to develop an instrument to measure adolescents’ perceptions of the role of parents as faith educators in Christian families, based on the principles found in Deuteronomy 6:6–9. In facing the challenges of the VUCA (Volatility, Uncertainty, Complexity, Ambiguity) era, the family—especially parents—plays a critical role in instilling strong faith values from an early age. This research applied a theoretical development method that included constructing a blueprint, drafting item statements, validating content through expert judgment, and testing the instrument on 260 university students. Content validity was analyzed using Aiken’s V index, while item validity was examined through the Pearson Product-Moment Correlation. All 26 items were found to be valid (r > 0.138), and the instrument demonstrated excellent reliability with a Cronbach’s Alpha value of 0.976. The Kaiser-Meyer-Olkin (KMO) value of 0.942 indicated that the data were suitable for further factor analysis. Based on the validation and reliability results, two items were removed, resulting in a final instrument with 24 valid and reliable statements. This instrument can be effectively used to assess adolescents' perceptions of their parents’ role in faith education. Future studies are recommended to conduct exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) to strengthen the theoretical and structural foundation of the measurement model. Bahasa Indonesia Abstract Penelitian ini bertujuan mengembangkan sebuah instrumen untuk mengukur persepsi remaja tentang peran orang tua sebagai pendidik iman dalam keluarga Kristen, berdasarkan prinsip-prinsip yang ditemukan dalam Ulangan 6:6–9. Dalam menghadapi tantangan era VUCA (Volatilitas, Ketidakpastian, Kompleksitas, Ambiguitas), keluarga—terutama orang tua—memegang peranan penting dalam menanamkan nilai-nilai iman yang kuat sejak usia dini. Penelitian ini menerapkan metode pengembangan teori yang meliputi penyusunan kerangka kerja, penyusunan pernyataan item, validasi isi melalui penilaian ahli, dan pengujian instrumen pada 260 mahasiswa. Validitas isi dianalisis menggunakan indeks V Aiken, sedangkan validitas item diuji melalui Korelasi Product-Moment Pearson. Semua 26 item dinyatakan valid (r > 0,138), dan instrumen menunjukkan reliabilitas yang sangat baik dengan nilai Cronbach’s Alpha sebesar 0,976. Nilai Kaiser-Meyer-Olkin (KMO) sebesar 0,942 menunjukkan data layak untuk dilakukan analisis faktor lebih lanjut. Berdasarkan hasil validasi dan reliabilitas, dua item dihapus sehingga instrumen akhir terdiri dari 24 pernyataan yang valid dan reliabel. Instrumen ini dapat digunakan secara efektif untuk menilai persepsi remaja terhadap peran orang tua dalam pendidikan iman. Studi lanjutan disarankan untuk melakukan analisis faktor eksploratori (EFA) dan analisis faktor konfirmatori (CFA) guna memperkuat landasan teoritis dan struktural model pengukuran.